2021
DOI: 10.1186/s40035-021-00244-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cerebrospinal fluid amyloidogenic nanoplaques with cytokines in Alzheimer’s disease

Abstract: Background The aggregation of amyloid β (Aβ) is central in the pathogenesis of Alzheimer’s disease (AD). Recently it has been shown that specifically, larger, Thioflavin T-binding Aβ aggregates are associated with increased neuroinflammation and cytokine release. This study was aimed to quantify fibrillary amyloid aggregates, so-called nanoplaques, and investigate their relationship with cytokines in the cerebrospinal fluid (CSF). Methods CSF was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…Cytokine and nanoplaque levels were not associated in serum, in contrast to previous findings in CSF in a different patient cohort [ 14 ]. This suggests that while CSF nanoplaques appear to be associated with markers of neuroinflammation, serum nanoplaques are not good indicators of cytokine-driven systemic inflammatory or anti-inflammatory activity.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Cytokine and nanoplaque levels were not associated in serum, in contrast to previous findings in CSF in a different patient cohort [ 14 ]. This suggests that while CSF nanoplaques appear to be associated with markers of neuroinflammation, serum nanoplaques are not good indicators of cytokine-driven systemic inflammatory or anti-inflammatory activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Most notably, the cohort is small to begin with (49 patients), and a major caveat in the interpretation of our data is that we only have complete biomarker profiles for a small subgroup (26 patients). However, in our previous research on the NorCog population we have found very high congruence between clinical- and biomarker-based classification of patients [ 14 ]. Furthermore, we do not have paired measurements of nanoplaque levels in CSF and serum from the same patient, and we cannot be certain of the composition of the quantified nanoplaques, which limits our interpretations as previously discussed.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations